Association between physician specialty and first-attempt intubation success in the emergency department - J. e Silva, Lucas Oliveira; Von Hellmann, Rafael; Besen, Bruno A.M. Pinheiro; de Carvalho, Julia M. Dorn; Hajjar, Ludhmila Abrahao; Pedrollo, Daniel; Nogueira, Caio Goncalves; Figueiredo, Natalia Mansur P.; Miranda, Carlos Henrique; Martins, Danilo [UNESP]; Baumgratz, Thiago Dias [UNESP]; Bergesch, Bruno; et al. (Wolters Kluwer, 2025)
BACKGROUND AND IMPORTANCE: Emergency airway management in the emergency department (ED) is a high-risk procedure associated with patient outcomes. First-attempt success is a widely recognized quality metric, as multiple attempts are associated with an increased risk of peri-intubation complications. In Brazil, where emergency medicine is a recently established specialty, many ED are staffed by physicians without formal emergency medicine training. The association between emergency medicine training and intubation outcomes in this setting has not been well characterized. OBJECTIVE: To assess the association of physician specialty with first-attempt success and immediate peri-intubation complications in Brazilian EDs. DESIGN: Secondary analysis of a multicenter, prospective cohort study from the Brazilian Airway Registry Cooperation. SETTING AND PARTICIPANTS: This study included adult patients who underwent tracheal intubation in EDs between March 2022 and April 2024. Patients were excluded if the intubation occurred outside the ED, during cardiopulmonary resuscitation, or for elective procedures. Intubations performed by medical students were also excluded. Physicians were categorized by specialty as emergency medicine or nonemergency medicine. OUTCOME MEASURES AND ANALYSIS: The primary outcome was first-attempt success; secondary outcomes included peri-intubation complications (severe hypoxemia, hemodynamic instability, and cardiac arrest). Multivariable logistic regression was used to assess the association between physician specialty and outcomes. MAIN RESULTS: Among 2582 patients, 1087 (42.1%) were intubated by emergency physicians and 1495 (57.9%) by other physicians (mainly internal medicine and surgery). Intubations by emergency physicians were associated with a higher rate of first-attempt success [80.4 vs. 70.9%, adjusted odds ratio [aOR]: 1.63, 95% confidence interval (CI): 1.34-1.97]. There was also a higher odds of intubations without major complications (aOR: 1.20, 95% CI: 1.01-1.42). CONCLUSION: In this study, there was a higher rate of first-attempt success in intubations performed by board-certified emergency physicians compared with other physicians working in Brazilian EDs.